2015
DOI: 10.1080/00222895.2015.1073137
|View full text |Cite
|
Sign up to set email alerts
|

Novel Kinetic Strategies Adopted in Asymmetric Split-Belt Treadmill Walking

Abstract: The hip and ankle strategies that affect learning of a novel gait have not been fully determined, and could be of importance in design of clinical gait interventions. The authors' purpose was to determine the effects of asymmetric split-belt treadmill walking on ankle and hip work during propulsion. Participants were randomized into either a gradual training group or a sudden training group and later returned for a retention test. The gradual training group performed significantly more work at the hip joint of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Late transfer windows included the last 20 strides of the transfer test. We have previously shown that some lower-limb kinetic adaptations are apparent early in an asymmetric walking bout, but do not persist until the end ( Hinkel-Lipsker and Hahn, 2016b ). Hence, analysis of gait mechanics during late transfer would show any persistent gait adaptations.…”
Section: Methodsmentioning
confidence: 99%
“…Late transfer windows included the last 20 strides of the transfer test. We have previously shown that some lower-limb kinetic adaptations are apparent early in an asymmetric walking bout, but do not persist until the end ( Hinkel-Lipsker and Hahn, 2016b ). Hence, analysis of gait mechanics during late transfer would show any persistent gait adaptations.…”
Section: Methodsmentioning
confidence: 99%
“…The split-belt treadmill approach has also been modified to determine whether sudden or gradual deviation from tied-belt to split-belt has any effect on participant performance. Hinkel-Lipsker and Hahn [5] conducted an experiment where one group was brought from tied-belt (0.7 m/s) to 2:1 split-belt (1.4 m/s to 0.7 m/s) by an acceleration profile of 0.02 m/s 2 every 20 strides and a second group by an acceleration profile of 10 m/s 2 . This experiment revealed a novel kinetic pattern at the hip joint of those trained with the gradual split belts.…”
Section: Split-belt Treadmill Trainingmentioning
confidence: 99%